Influence of needle and irrigation flow rate on root canal cleaning and apical extrusion of irrigant: Micro-CT analysis - Torres, Fernanda Ferrari Esteves [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Oliveira, Luna do Val [UNESP]; Chaves-Andrade, Gisselle Moraim [UNESP]; Tanomaru-Filh, Mario [UNESP] (Dental Press International, 2021)
Introduction: needle and irrigation flow rate are important for proper cleaning of the root canal. Aim: to evaluate the influence of type of needle and irrigation flow rate on cleaning of root canal and simulated lateral canals and the apical extrusion of irrigant. Methods: Thirty-two resin teeth were used. After root canal instrumentation, four lateral canals were made at 2 and 7 mm from the apex. Root canals were filled with contrast solution. The root canals were irrigated with two types of needle, 29G and 31G, with different designs (side and apical opening) and two flow rates (2 or 5 mL/min), at 1 mm short of the working length. The volume of the contrast solution in the main and lateral canals after irrigation and apical extrusion of the irrigant (mm3) were evaluated by Micro-CT, in comparison with the initial analysis. Data in percentage were analyzed by ANOVA and Tukeys tests (α = 0.05). Results: no difference among the irrigation protocols for contrast solution cleaning was observed. Higher volume of apical extrusion using needle 29G-apical opening and 5 mL/min in comparison with the same type of needle and 2 mL/min was observed (p < 0.05). Conclusion: all irrigation protocols were associated with root canals cleaning. Greater apical extrusion was observed for needle 29G-apical opening with higher irrigation flow rate (5 mL/min). Clinical implications: endodontic irrigation using a needle with apical opening and higher flow rate of solution may favor extrusion of irrigant to the periapical tissues.
Keywords: Endodontics; Root canal preparation; Therapeutic irrigation; X-ray microtomography